Spatial impact of the built environment on street vitality: A case study of the Tianhe District, Guangzhou - Wangbao, Liu (Frontiers in Environmental Science, 2022)
Taking the Tianhe District in Guangzhou as an example and the urban street (road) as the basic research unit and using Tencent location service data to characterise street vitality, this study established the urban built environment index and uses OLS and GWR models to construct the statistical relationship between the built environment and street vitality to analyse the influencing factors of street vitality. It was found that spatial heterogeneity was considered in the GWR model based on local geographic weighting, and its fitting effect was better than that of the OLS model, which can reveal the micro-local characteristics of the built environment’s effect on street vitality. Increasing the land-use mixing degree, new and old building mixing degree, and use intensity (building density and volume ratio) can significantly increase street vitality, which proves to a certain extent that Jacobs's relevant discussion is still highly practical for the Tianhe District.